Review of the yellow-bodied species of the genus Timia (Diptera: Ulidiidae) with description of two new species - Galinskaya, Tatiana V. (Zootaxa, 2011)
Seven species of Timia Wiedemann, 1824, differing from the rest of members of this genus by yellow body are reviewed. All of them, including two new species are described and figured. Timia (Timia) zaitzevi Galinskaya sp. nov. from Kazakhstan is similar to T. (T.) testacea Portschinsky, 1892, differing by the presence of a short postero-dorsal extension of the cell bcu (not longer than the width of cell bcu), and by the presence of a silvery-white microtrichosity on mesonotum, with rows of confluent shining spots around the base of setae. Timia (Empyelocera) flaveola Galinskaya sp. nov. from Turkmenistan is similar to T. (E.) orientalis Zaitzev, 1982, but differs by the presence of a silvery-white microtrichosity on mesonotum, without confluent shining spots around bases of setae. Lectotypes are designated for Timia (Timia) testacea Portschinsky, 1892 and Timia (Empyelocera) canaliculata Becker, 1906. A key to eight species (including T. (E.) berlandi Séguy, 1953), descriptions and illustrations are provided.